The effect of the ethyl acetate extract of Eleutherine bulbosa on reducing cholesterol in male white rats - Miming Andika; Haliza Diny Fauzia; Oktavianis; Rizqa Hasanah; Nanda Hasanah; Oryza Sativa Fitriani; Fajrian Aulia Putra; Nur Rahmi; Taufit Julianto (Pharmaciana, 2026)
Heart disease and stroke are more likely to occur in people with high cholesterol. Hypercholesterolemia is the cause of one-third of ischemic heart disease worldwide. One of the plants cultivated by communities for traditional medicine is Eleutherine bulbosa, which is used to treat cardiovascular conditions. E. bulbosa has antioxidants, which can lower cholesterol levels by competitively inhibiting the enzyme HMG-CoA reductase, thereby reducing cholesterol formation in the liver. E. bulbosa also contains flavonoids, whose role in lowering hypercholesterolemia is by reducing HMG-CoA reductase activity and increasing lecithin cholesterol acyl transferase (LCAT) activity, which accelerates the reaction of cholesterol ester formation from free cholesterol in high-density lipoprotein (HDL) molecules during the process of cholesterol uptake from cells or tissues, and decreases liver HMG-CoA reductase enzyme levels. This study aimed to examine the effects of administering the ethyl acetate fraction of E. bulbosa and test its ability to reduce total cholesterol, LDL, VLDL, and triglycerides, while increasing HDL. The test animals were fed a high-fat diet for 22 days to increase their cholesterol levels. A Dumolab DC20 photometer was used to measure cholesterol levels. Histopathological examination of the aorta was performed using paraffin blocks and stained with hematoxylin and eosin. The preparations were observed under a microscope (magnification of 100x and 400x). Observations included the diameter of the aorta. The results showed that the treatment groups differed significantly (P < 0.05). According to Duncan's test, there was a difference in reduction, in the hypercholesterolemia + extract group, the decrease in cholesterol levels was lower compared to the hypercholesterolemia + simvastatin group. The most effective dose group was 400 mg/kgBW, which was close to the results of the hypercholesterolemia + simvastatin group. Administration of the ethyl acetate fraction of E. bulbosa can normalize cholesterol levels. Also, histopathological results showed that the diameter of the aorta was larger after administration of 400 mg/kgBW of E. bulbosa extract compared to the hypercholesterolemia group.